Consumption of ultra-processed foods among children aged 6 to 23 months as per the Second National Survey on Nutrition and Health of Argentina - Armani, María Florencia (2023)
Introduction. The availability of data on the consumption of ultra-processed foods among children is important for planning public policies. Objectives. To describe the prevalence of consumption of ultra-processed foods in children under 2 years of age and identify associated factors. To describe the proportion that ultra-processed foods represent out of the total number of foods consumed in a day. Methods. Secondary analysis of data from children aged 6-23 months with at least a 24-hour recall of food consumption based on the Second National Survey on Nutrition and Health of Argentina (2018). The following primary variables were studied: "consumption of ultra-processed foods" (according to the NOVA system) categorized into yes/no and "proportion of ultra-processed out of total foods consumed." The following associated factors were studied: breastfeeding, sex, age, and number of non-ultra-processed foods consumed. A multivariate logistic regression model was developed and an expansion factor was applied to weight the data. Results. A total of 4224 children were included (weighed: 908 104). The prevalence of ultra-processed food consumption was 90.8% (95% CI: 89.5-92) and was associated with an older age (OR: 3.21, 95% CI: 2.28-4.52) and the number of non-ultra-processed foods consumed (OR: 1.17, 95% CI: 1.13-1.23). Ultra-processed foods accounted for a median 20% (IQR: 12.5-28.6%) of all foods consumed in a day. Conclusions. This study highlights the high penetration of ultra-processed foods in complementary feeding.